2021
DOI: 10.1364/ol.441285
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light extraction of the deep-ultraviolet micro-LED via rational design of chip sidewall

Abstract: In this Letter, we perform a comprehensive investigation on the optical characterization of micro-sized deep-ultraviolet (DUV) LEDs (micro-LEDs) emitting below 280 nm, highlighting the light extraction behavior in relation to the design of chip sidewall angle. We found that the micro-LEDs with a smaller inclined chip sidewall angle ( ∼ 33 ∘ ) have improved external quantum efficiency (EQE) performance 19% more than that of the micro-LEDs with a larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In contrast, as shown in Figure 5b,c, parts of the DUV photons in the MC‐LEDs could transmit into the MC structure and be effectively reflected back to the substrate side, diminishing the TIR effects. Moreover, based on our previous report, [ 28,33,34 ] the increased proportion of the sidewall of the MC‐LEDs would also help to reflect more light toward the backside of the LEDs, and the downsize area of p‐GaN decreases the self‐absorption of photons. Hence, the opportunity for the DUV photons in the MC‐LEDs to escape from the sapphire substrate side increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, as shown in Figure 5b,c, parts of the DUV photons in the MC‐LEDs could transmit into the MC structure and be effectively reflected back to the substrate side, diminishing the TIR effects. Moreover, based on our previous report, [ 28,33,34 ] the increased proportion of the sidewall of the MC‐LEDs would also help to reflect more light toward the backside of the LEDs, and the downsize area of p‐GaN decreases the self‐absorption of photons. Hence, the opportunity for the DUV photons in the MC‐LEDs to escape from the sapphire substrate side increases.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19–21 ] With a slew of efforts in recent years, great progress has been made in materials quality [ 22,23 ] and doping asymmetry issues, [ 24–27 ] and nowadays the poor light extraction efficiency (LEE) becomes the main bottleneck to further improve the output power of DUV LEDs. To mitigate these issues earlier, various strategies have been proposed, such as inclined sidewalls, [ 28 ] surface roughing, [ 29 ] and microscale structure [ 30 ] including microlens, [ 31 ] the hybrid microscale patterned sapphire substrates, [ 32 ] and micro‐LED design. [ 33,34 ] On the other hand, a series of designs have been proposed to enlarge the modulation f 3dB of the DUV LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the deep UV μLEDs with a smaller inclined chip sidewall angle (≈33°) have improved EQE performance 19% more than that of with a larger angle (≈75°). [ 151 ] On October 5, 2021, Nitride Semiconductors has announced that patent on high efficiency technology for UV μLEDs were granted in the USA (Patent number: 11,139,342). Nitride's new patented technology improves luminous efficiency in UV μLED chips mainly using a superlattice structure and PSS.…”
Section: Recent Advances In Packaging Technologiesmentioning
confidence: 99%
“…Nanostructures, nitride-based alloys [ 9 ], quantum barrier structures such as graded quantum barriers [ 10 ], and quantum wells [ 11 ] have been studied to emit in the DUV range, improving the efficiency. Recently, also micro-LEDs have been explored [ 12 , 13 ], resulting in the device size reduction by a light extraction improvement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%